2021
DOI: 10.48550/arxiv.2111.05100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EEGEyeNet: a Simultaneous Electroencephalography and Eye-tracking Dataset and Benchmark for Eye Movement Prediction

Abstract: We present a new dataset and benchmark with the goal of advancing research in the intersection of brain activities and eye movements. Our dataset, EEGEyeNet, consists of simultaneous Electroencephalography (EEG) and Eye-tracking (ET) recordings from 356 different subjects collected from three different experimental paradigms. Using this dataset, we also propose a benchmark to evaluate gaze prediction from EEG measurements. The benchmark consists of three tasks with an increasing level of difficulty: left-right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…EEGEyeNet Dataset: For all experiments, we used EEGEyeNet [16] dataset and benchmark that includes synchronized Electroencephalography (EEG) and Eye-tracking recordings, obtained during an experiment where participants were instructed to follow a series of successively appearing dots on a 24-inch monitor placed at a distance of 68cm. A stable head position of the participant was ensured via a chin rest.…”
Section: Materials and Experimental Settingsmentioning
confidence: 99%
See 3 more Smart Citations
“…EEGEyeNet Dataset: For all experiments, we used EEGEyeNet [16] dataset and benchmark that includes synchronized Electroencephalography (EEG) and Eye-tracking recordings, obtained during an experiment where participants were instructed to follow a series of successively appearing dots on a 24-inch monitor placed at a distance of 68cm. A stable head position of the participant was ensured via a chin rest.…”
Section: Materials and Experimental Settingsmentioning
confidence: 99%
“…EEGEyeNet Dataset: For our experiments, we utilized the EEGEyeNet dataset [16], which includes synchronized EEG and Eye-tracking data. The EEG signals were collected using a high-density, 128-channel EEG Geodesic Hydrocel system sampled at a frequency of 500 Hz.…”
Section: Materials and Experimental Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers from Computer Science, Neuroscience, and Medical fields have applied EEG-based Brain-Computer Interaction (BCI) techniques in many different ways [2,15,19,22,24,26,34], such as diagnosis of abnormal states, evaluating the effect of the treatments, seizure detection, motor imagery tasks [4,5,6,17,23,27], and developing BCI-based games [14]. Previous studies have demonstrated the great potential of machine learning, deep learning, and transfer learning algorithms [1,3,7,8,12,16,18,20,21,25,28,29,37,38,39,40,41,42] in such clinical and non-clinical data analysis.…”
Section: Introductionmentioning
confidence: 99%